First Nations Children Count: Enveloping Quantitative Research in an Indigenous Envelope - Blackstock, Cindy (First Peoples Child & Family Review, 2009)
Indigenous peoples repeatedly call for disaggregated data describing their experience to inform socio-economic and political policy and practice change (United Nations Permanent Forum on Indigenous Issues, 2003; UNICEF, 2003; Rae & the Sub Group on Indigenous Children and Youth, 2006). Although there has been significant discourse on the destructive historical role of western research with Indigenous communities (RCAP, 1996; Smith, 1999; Schnarch, 2004) and more recently on cultural adaptation of qualitative research methods (Smith, 1999; Bennet, 2004; Kovach, 2007), there has been very little discussion on how to envelope western quantitative social science research within Indigenous ways of knowing and being. This paper begins by outlining the broad goals of Indigenous research before focusing on how quantitative research is used, and represented, in the translation of Indigenous realities in child health and child welfare. Given the rich diversity of Indigenous peoples and their knowledges, this paper is only capable of what respected Indigenous academic Margo Greenwood (2007) would term “touching the mountaintops’ of complex and sacred ideas.